A High-Gain CNTFET-Based LNA Developed Using a Compact Design-Oriented Device Model - Paolo Crippa (MDPI AG, 2021)
Recently, carbon nanotube field-effect transistors (CNTFETs) have attracted wide attention as promising candidates for components in the next generation of electronic devices. In particular CNTFET-based RF devices and circuits show superior performance to those built with silicon FETs since they are able to obtain higher power-gain and cut-off frequency at lower power dissipation. The aim of this paper is to present a compact, design-oriented model of CNTFETs that is able to ease the development of a complete amplifier. As a case study, the detailed design of a high-gain CNTFET-based broadband inductorless LNA is presented.